Five Decades of Union Wages, Nonunion Wages, and Union Wage Gaps at Unionstats.com - David A. Macpherson; Barry Hirsch (Institute of Labor Economics (IZA), 2021)
Union, nonunion, and overall wages, plus regression-based union wage gap estimates, are provided annually, beginning in 1973 using the Current Population Surveys (CPS). The estimates are presented economy-wide by demographics and sectors (private/public, industries). Union wage gaps are higher in the private than in the public sector, higher for men than women, roughly similar for black and white men, and much higher for black than for white women. We estimate mean weekly earnings above CPS topcodes by gender and year, assuming a Pareto distribution in the right tail of the distribution. The database is online and will be updated annually.
Keywords: J31; J51; C81; 330; earnings; union wage gaps; CPS topcodes